Studying the Knowledge, Attitude, and Practice of HealthCare Workers Towards Hepatitis B Virus Prevention in Hospitals, Hodeidah City, Yemen, 2024 - Taha, Mogeeb Saeed; Al-Wesabi, Sadeq Abdo Mohammed; Al-Selwi, Khaled; Suhail, Mohammed Ahmed; Al-Nahary, Radman Ahmed; Baalwi, Abdulaziz Ahmed; Ghanim, Nabil Ahmed Saif (Journal of medical and pharmaceutical sciences, 2024)
Background: Hepatitis B virus (HBV) infection is a public health problem. Healthcare workers (HCWs) are at a high risk for blood-borne pathogens due to their contact with patients and contaminated instruments. Vaccination of HCWs against HBV is standard practice in many countries but is often not implemented in resource-poor settings. to determine HBV knowledge attitude and practice, a study conducted in Al-Mukalla City a majority of participants had poor knowledge and practice about hepatitis B and its management. Also, the vast majority had a negative attitude toward hepatitis B virus .Objective: The purpose of this study was to evaluate the knowledge, attitude, and practice (KAP) of HCWs towards hepatitis B infection in Hospitals, Hodeidah city.  Methodology: We enrolled 290 HCWs from the main public and privet hospitals (Athwrah and Alamal Hospitals). Their demographics, medical histories, HBV vaccination details and risk factors for contracting blood-borne infections were collected using a standardized questionnaire. The study was conducted during the period of 1st of March to 1st of May 2024 . Results: The overall KAP scores of HCWs were found to be 20%, 99.7%, and 30%,were positive respectively. Most of the participants correctly recognized the HBV infection. Among the participants, only 15% had undergone screening for HBV, and 43.8% had received HBV vaccine. Moreover, only 43% had completed the three doses of vaccination for HBV. Among the HCWs, the group with higher education level had better knowledge than the group with lower education level. However, the attitude of most of the participants towards HBV prevention was found to be adequate . (99.7%). Conclusion: This study shows that HCWs in Hodeidah, Yemen is at high risk of HBV infection due to low vaccination coverage and inadequate infection control. Therefore, we strongly encourage providing an accessible and compulsory vaccination program for all HCWs to improve their attitude and awareness towards HBV infection and to achieve effective infection control.
Keywords: HBV; HBc; Health workers; Hodiedah; Yemen